A Study on Effects of Fertilization and Supplementary Feed on Growth Performance of Three Indian Major Carps - Prabaharan, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTThe present study was aimed to evaluate the growth performance in terms of average body weight, specific growth rate and total fish production of these fishes for one year, a polyculture experiment was carried out on the Rohu (Labeo rohita Ham.), Catla (Catla catla Ham.) and Common carp (Cyprinus carpio Ham). The ponds were supplemented with 0.2 g N/100 g body weight fertilizer and supplementary feed, the sources of which were different. The treatments were cow manure, nitrophos, cow manure + nitrophos, cow manure + supplementary feed, nitrophos + supplementary feed and cow manure + nitrophos + supplementary feed. The highest gross fish production of all the fishes was recorded as 3001 kg ha-1 year-1 in cow manure + nitrophos + supplementary feed amongst the treatments. Thus for getting optimal fish production the fertilization of pond with supplementary feed is recommended.